Cumulative mortality effects on roe deer population dynamics in the boreal forest: Searching for pathways of population persistence - Cécile A.E. Carpentier; Marco Heurich; Olivier Gimenez; Olivier Devineau; John D.C. Linnell (Global Ecology and Conservation)
Ungulate populations can exhibit various growth patterns, which are influenced by factors such as predation and resource availability. Favourable environments can lead to irruptive growth, resulting in resource depletion. However, additional pressures from predation, and hunting can potentially impact population development leading to declines or even local extinctions. This study uses simulation models to explore the potential impact of multiple mortality sources on roe deer populations. We develop an age-structured, two-sex demographic matrix model for roe deer, which we parameterise with empirical demographic estimates obtained from published studies in Norway. We develop scenarios to assess the influence of mortality sources such as hunting, predation by lynx and red foxes, and environmental stochasticity on roe deer population dynamics. When simulating favourable environments without predation, roe deer populations tended to erupt due to the species' rapid reproductive capacity. However, additional sources of mortality, such as predation or harvest, lead to severe population declines, and even to quasi-extinction, especially when occurring in combination. Environmental stochasticity such as periodic severe winters with heavy snowfall reduces the growth rate and population densities even further. On the other hand, accounting for some form of spatial heterogeneity through immigration and refuges stabilised populations, with a reduced risk of quasi-extinction. Our results provide meaningful insights into the properties of this system allow implications for the management and identify areas where further exploration is needed.